Market Mechanisms Elements of Effectiveness and Quality Increase of Region's Recreation Services in the Health Resort and Touristic Cluster - Igor N. Molchanov; Natalia P. Molchanova; Maria A. Gureva; Boris M. Zhukov; Elena A. Gorlova (International Review of Management and Marketing, 2016)
It should be mentioned that the creation and development of resort and tourist space crafters is limited by the presence of a number of socio-political and economic problems, which are aggravated by macroeconomic instability. Resource potential recreational areas today is underutilized and poorly understood. The poor quality of the services provided, the price uncompetitive in comparison with foreign resorts, obsolete and outlived a main fund, the weak diversification of services in the recreational area, a long stagnation in the development of inbound and domestic tourism, low development of recreational infrastructure, etc. are signs that the recreational sector requires more attention. Improving the efficiency and quality of recreational services in the resort and tourist cluster in the region is an urgent and difficult problem of the region's economy. One of the main directions in improving the efficiency and quality of recreational services we can assume formation and rational use of the recreational potential of the region. Formation of the defining trends of resort and tourist activities based mainly on the development of economic space in the region, which is a rich area, which includes a set of objects that interact with each other. Activities of the resort and tourism cluster is the entire socio-economic system, which are exposed to various factors, the role and influence of which can be under certain conditions, varying in strength, direction and pro-expectancy. Identification, analysis and classification of the factors of increasing the efficiency of recreational service deserve special attention in the development of resort and tourist cluster in the region.